Pengaruh Store Atmosphere terhadap Kepuasan Konsumen di antar Ruang Coffee & Eatery - Noegraha, Rosandi Ardi; Latif, Latif; Sari Harsanti, Pradnya; Sari Wardhan, Hilda (CV. Creative Tugu Pena, 2024)
This research was aimed at finding out how the Store Atmosphere affects consumer satisfaction at Antar Ruang Coffee & Eatery. This research uses a questionnaire as a tool in collecting respondent data. The analysis technique used is quantitative descriptive analysis. The population and sample in this research were visitors to Antar Ruang Coffee & Eatery. The number of respondents in this research was 100 respondents. The results of this research are based on simple linear regression analysis to obtain a sig number. < 0.05, then the store atmosphere variable has a significant influence on the consumer satisfaction variable with an R squre of 0.354, meaning that the store atmosphere influences consumer satisfaction by 35.4% and the remaining 64.6% is influenced by other factors. Keywords: Store Atmosphere on Consumer, Consumer Satisfaction